BCL-2 and p53 expression in endometrial carcinoma - (:unkn) unknown (APSIT ASSOC PROM STUD IMMUNOL TUMOR, 2004)
Our aim was to compare the results of bcl-2 expression in endometrial carcinoma with clinicopathological prognostic factors along with p53 accumulation. In addition, p53 expression was compared to different subtypes of endometrial carcinoma. Immunohistochemical staining was pet-formed on formalin-fixed, paraffin embedded tissue sections by using Bcl-2 Supersensitive Mouse Anti-Bcl-2 Oncoprotein (Biogenex AM287-5M) for bcl-2 immunostaining and Supersensitive Mouse Anti-p53 Suppressor Gene Product (1801) (Biogenex AM 240-5M) for p53 immunostaining. 9 out of 9 cases of proliferative endometrium, 515 cases of endometrial hyperplasia without atypia, 515 cases with atypia, and 21/35 cases of endometrial carcinoma showed bcl-2 protein expression. Bcl2 expression was not related to age, surgical stage, or histopathological features, nor was there an inverse correlation between bcl-2 and p53 expression in endometrial carcinoma. p53 expression was detected in 3/4 cases of serous papillary carcinoma, whereas only 5/31 cases of endometrioid carcinoma showed p53 expression. Bcl-2 expression decreased in endometrial carcinomas, and mechanisms other than p53 may play a role in the regulation of bcl-2 expression in endometrial carcinoma. Abnormal p53 protein expression is an important event in the development of serous tumors, which may explain partly why they are more aggressive than their endometrioid counterparts where p53 expression does not play a major role.
Keywords: Bcl-2; p53; endometrial carcinoma; immunohistochemistry; MENSTRUAL-CYCLE; BREAST-CANCER; PROGNOSTIC INDICATOR; GENE-EXPRESSION; CELL SURVIVAL; B-CELLS; PROTEIN; OVEREXPRESSION; HYPERPLASIA; LYMPHOMA